Pengaruh Pendekatan Deep Learning Berbantuan E-Performance Rubric Terhadap Kemampuan Berpikir Kritis Siswa SMK - Komang Hari Santhi dewi; Rifky Lana Rahardian; I Made Pradipta; Ni Wayan Sri Jayanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of the Deep Learning approach assisted by an e-performance rubric on the critical thinking skills of tenth-grade vocational high school students in mathematics. The research employed a quasi-experimental method with a posttest-only control group design. The participants consisted of 40 students from SMK TI Global Jimbaran, divided into two groups: an experimental group that received instruction using the Deep Learning approach supported by a digital performance rubric, and a control group that received conventional teaching, with 20 students in each group. Critical thinking skills were measured using a validated essay test that included indicators of inference, analysis, evaluation, explanation, and self-regulation. Data analysis involved normality testing, homogeneity testing, and an Independent Samples t-test. The results revealed that the implementation of the Deep Learning approach assisted by the Authentic Digital Performance Assessment (ADPA) had a significant effect on students’ critical thinking skills. Students who received the intervention demonstrated higher learning outcomes compared to those who were taught using conventional methods. These findings emphasize that integrating the Deep Learning approach with digital performance assessment can serve as an effective instructional strategy in vocational education contexts